(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
The research aims to demonstrate the impact of the negative relationship of double deficits in increasing structural imbalances and reducing economic growth in Iraq. To achieve this goal, the deductive approach was used through the descriptive analytical method to analyze data on the general budget deficit and the trade balance deficit, along with analyzing the components of the gross domestic product and average per capita income for the period (2003-2022). With the help of the quantitative analytical method using the ARDL model to measure the impact of the dual general budget deficit and the trade balance deficit on the gross domestic product, Accordingly, it was concluded that the double deficit is related to the decline in real growth and that growth in Iraq is a result of the rise in oil revenues. Therefore, decision-makers must reconsider current adopt compatible economic policies for investment directed towards increasing the productive base of the economy to supplement the gross domestic product, and then increase Merchandise exports and achieving self-sufficiency and real economic growth.